2017
DOI: 10.1097/mib.0000000000001104
|View full text |Cite
|
Sign up to set email alerts
|

miR-4728-3p Functions as a Tumor Suppressor in Ulcerative Colitis-associated Colorectal Neoplasia Through Regulation of Focal Adhesion Signaling

Abstract: Background As mechanisms of neoplasia in patients with ulcerative colitis (UC) remain poorly understood, we sought to identify pathways of carcinogenesis in this high-risk population. Methods miRNA and mRNA expression was examined in non-dysplastic rectosigmoid mucosa from UC patients with (n=19) or without remote colon neoplasia (n=23). We developed a method to identify miRNA-regulated pathways based on differentially expressed miRNAs and their putative mRNAs targets in the same samples. One key pathway ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…8a). Among the miRNAs, we mainly focus on miR-125a-5p [35,36], miR-760 [37,38], miR-4728-5p [39,40] and miR-6785-5p [40], knowing that they are closely correlated with other malignancies.…”
Section: Lncrna Mnx1-as1 Mediated Gc Progression By Repressing the Exmentioning
confidence: 99%
“…8a). Among the miRNAs, we mainly focus on miR-125a-5p [35,36], miR-760 [37,38], miR-4728-5p [39,40] and miR-6785-5p [40], knowing that they are closely correlated with other malignancies.…”
Section: Lncrna Mnx1-as1 Mediated Gc Progression By Repressing the Exmentioning
confidence: 99%
“…CRP and COL12A1, which were among the 78 SNT-related differentially regulated proteins, did not directly interact but they may interact through their downstream/upstream proteins, such as FBLN2, LAMA5, THBS2 (which may play a crucial role in UC progression and may be a novel prognostic biomarker ( Chang et al, 2016 ; Pekow et al, 2017 ), and APOE [which may increase susceptibility to UC ( Keshen et al, 2009 )].…”
Section: Discussionmentioning
confidence: 99%
“…Among the enriched signaling pathways, activation of the Ras‐Raf‐MAPK pathway was reported to be involved in the pathogenesis, progression, and oncogenesis of human colorectal cancer . Other studies found that miR‐4728‐3p functions as a tumor suppressor in colitis‐associated colorectal neoplasia through the regulation of focal adhesion signaling …”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] Other studies found that miR-4728-3p functions as a tumor suppressor in colitis-associated colorectal neoplasia through the regulation of focal adhesion signaling. 42…”
Section: The Circrna Expression Profile In An Aom/dss Induced Colitmentioning
confidence: 99%